Mental Health Staff Perspectives on Personal Recovery: A Narrative Study on Positive Professional Impact of Recovery-Oriented Care - Kirkegaard Thomsen, Dorthe; Østergaard Christensen, Torben; Tranberg Hansen, Marie; Slade, Mike (Journal of Recovery in Mental Health, 2024)
ObjectivesMental health staff play an important role in facilitating personal recovery. We examined how mental health staff perceived personal recovery and the professional and personal benefits of their experience with supporting the personal recovery of service users.Research Design and MethodsForty-eight mental health staff wrote a narrative about a service user with severe mental illness that they believed to be in the process of personal recovery and elaborated on the impact of this professional experience. Interpretive phenomenological analysis was used to illuminate 1) staff conceptualizations of personal recovery, 2) professional contribution to recovery, and 3) positive impactof recovery-oriented care on staff.ResultsStaff conceptualizations of recovery focused on social connections and positive subjective states, as well assymptom remission and illness management. Professional contributions were narrated as encompassing treatment, relationships, and conversations as well as time and team collaboration. Impact on the staff included strong positive emotions, professional gains with respect to learning and self-esteem, motivation for and meaning in work, as well as belief in recovery.ConclusionsThis latter finding suggests that sharing narratives about service users in the process of personal recovery may increase work pleasure and help reduce burnout in mental health staff.